PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN, KEPUTUSAN PENDANAAN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Elvy Nugraheni; Darmanto Darmanto; Yuwita Ariessa (CV. Denasya Smart Publisher, 2025)
This study was conducted to understand the impact of profitability, dividend policy, funding decisions and investment decisions on the value of Food and Baverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 - 2024. The research method used is quantitative method. The data collection method used is the literature study technique and the official website (bei.go.id). The population studied in this study were all Food and Baverage companies listed on the IDX in 2021-2024. Data collection in this study was carried out using purposive sampling technique, obtained a sample of 108, but the actual sample studied was 101 companies due to the emergence of data with extreme values. The test method in this study uses descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis testing, namely the f test, t test and coefficient of determination test. The F test gets a significance value of 0.000 <0.05 so that the model is feasible to study. The t test results of this study are profitability and investment decisions affect firm value. This is evidenced by the significance value of 0.000 <0.05. Conversely, dividend policy has no effect on firm value, as evidenced by the t value of 1.283 < t table 1.98498 and a significance value of 0.203> 0.05. Then the funding decision with a t value of 1.914 < t table 1.98498 with a significance value of 0.059 > 0.05 so that the funding decision does not affect the company's value. From the results of the coefficient of determination test, the results are 0.800, which means that the profitability variable, dividend policy, funding decisions and investment decisions in explaining the company's value are 80.0% and the remaining 20.0% is explained by other variables